Transcriptomic and targeted metabolomic analysis identifies genes involved in differential anthocyanin accumulation in potato tubers - Yang, Rui; Huang, Shuohan; Li, Dan; Sun, Yuan; Zhou, Guangdong; Zhou, Duanrong; Huang, Binquan (Frontiers in Plant Science, 2025)
Purple-fleshed potatoes accumulate high amounts of anthocyanins, which are beneficial to human health. Although the biosynthesis of these secondary metabolites has been well studied in plants, the mechanisms underlying anthocyanin accumulation in different tissue regions of potato tubers remain less understood. To identify genes and metabolites involved in anthocyanin accumulation, we performed comparative transcriptomic and metabolomic analyses of pith and vasculature tissues from the tubers of three different potato cultivars. Anthocyanin-targeted metabolome analysis revealed that 20 anthocyanins were key metabolites conferring purple pigmentation in the tuber. Integrated transcriptomic and metabolomic analysis identified 1,924 genes potentially involved in multiple pathways for the biosynthesis of these anthocyanins. In particular, we identified 47 genes that were specifically expressed in the tuber and highly correlated with different anthocyanins. These genes were associated with ATP-binding cassette transporters and phytohormone pathways. Additionally, a core transcription factor, StWRKY44, involved in anthocyanin accumulation in the tuber was identified; it was capable of binding to and activating the promoters of 7 anthocyanin structural genes. This study provides insights into the genes and metabolites underlying anthocyanin accumulation in potato tubers, which will be valuable for future functional studies and breeding efforts.